ANALISIS PENGARUH SOLVABILITAS, BIAYO OPERASIONAL DAN KREDIT MACET TERHADAP PROFITABILITAS PERBANKAN PADA BANK-BANK YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2011-2015 - B31112063, DHEA NUR AISHAH (Jurnal Manajemen Update, 2017)
The purpose of this research to influence mrngetahui CAR, ROA and NPL to ROA banking companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2015. The sampling method used is purposive sampling method. The population in this research that all banking companies currently registered Indonesia Stock Exchange (BEI) in the period 2011-2015. Of the population of 40 banks acquired 23 banks in the sample with the observation period for 5 years from 2011-2015. Data analysis technique used is multiple linear regression analysis. The result showedÂ  that the CAR and no significant positive effect on ROA so that the first hypothesis is rejected. BOPO a significant negative effect on ROA so that the second hypothesis is accepted. NPL and no significant positive effect on ROA so that the third hypothesis is rejected. Keywords : ROA, CAR, BOPO, NPL